Study of the Recharge Area on Water Basin Soil with Remote Sensing Method Using Satellite Imagery Landsat 7 ETM + and Geographic Information Systems ( GIS ) (Case Study : Pasuruan District ) - Isniyatus Sholikhah; Muhammad Taufik; Kukuh Sudjatmiko (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
Water is natural resources that is very essential for living creatures and the environment. Along with the increase of population , will increase the water demand and reduce the area of free land / open green space for the formation of ground water. By considering soil water conservation aspects, it is necessary to conduct a study of the recharge area on water basin soil in Pasuruan. This study was to determine the condition of the recharge area in the Basin Groundwater Pasuruan in 2003 and 2014. So it will be k[1]nown the changes of the vegetations density and land cover in the recharge area that can affect infiltration process in order to conserve water resources in CAT Pasuruan. From these changes it would be able to make the prediction of future conditions in the recharge area in CAT Pasuruan. This study uses Remote Sensing using Satellite imagery Landsat and Geographic Information System (GIS). Studies to determine the recharge area is influenced by several parameters, that is slope of land, lithology and Rainfall. Processing results obtained vegetation density changes of the recharge area in 2003-2014, high vegetation density decreased by 4330,89 Ha, so that changes in the high vegetation density in 2025 is predicted to be 52305,39 Ha and become 52176,78 Ha in 2030. While land cover changes produce changes in forest land cover increased by 569,88 Ha , so that changes in forest land cover in 2025 is predicted to be 37563,88 Ha and became 38720,494 Ha in 2030. The relationship between vegetation density and land cover of the recharge area in 2003 - 2014 obtained high vegetation density that experienced an increase area, which is on garden land cover amounting to 1144,80 Ha, 943,02 Ha of forest, 947,79 Ha of settlements land cover and 262,53 Ha of vacant land. And that experienced an increase with low vegetation density are the fields amounting to 943,02 Ha and 277,47 Ha of vacant land. Land cover vegetations that dominates throughout the recharge area is a mahogany tree vegetation, and sengon.